Determination of cadmium (Cd) levels in soils and seeds of cocoa plantations (Theobroma cacao L.) in the ecuadorian highlands - Medina Rodríguez, Kléber Efraín (2026)
The purpose of the research was to determine cadmium (Cd) levels in cocoa crops (Theobroma cacao L.) at a production unit located in Bolívar Province, Ecuador. To this end, 10 soil samples were collected at a depth of 0 to 20 cm at different points on the farm. Cocoa pods were also collected from 10 trees at random at the sites where the soil samples were taken to determine the Cd content in the seeds using atomic absorption. The samples were georeferenced and mapped using ArcGIS 10.3 software based on contamination levels. Statistical analysis was performed using the one-tailed Student's t-test to compare with current standards on permissible cadmium levels in soil and European food regulations on Cd values in seeds. The results showed an average of 1.39 mg kg-1 in soils, which in no case exceeds the maximum permitted levels. In the case of seeds, Cd ranged from 0.19 to 1.11 mg kg-1, which is within the permitted range. Although the values found do not pose a risk to cocoa exports, preventive measures need to be taken, especially with regard to fertilization management, one of the main sources of Cd in the crop, in order to minimize the risks of Cd accumulation in soils and seeds, particularly in areas where the highest levels of this metal were reported.